2014
DOI: 10.4155/fmc.14.116
|View full text |Cite
|
Sign up to set email alerts
|

Mirna-Based Therapies: Strategies and Delivery Platforms for Oligonucleotide and Non-Oligonucleotide Agents

Abstract: The discovery of miRNAs as important regulatory agents for gene expression has expanded the therapeutic opportunities for oligonucleotides. In contrast to siRNA, miRNA-targeted therapy is able to influence not only a single gene, but entire cellular pathways or processes. It is possible to supplement downregulated or non-functional miRNAs by synthetic oligonucleotides, as well as alleviating effects caused by overexpression of malignant miRNAs through artificial antagonists, either oligonucleotides or small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
179
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(180 citation statements)
references
References 176 publications
(183 reference statements)
0
179
0
1
Order By: Relevance
“…Mitigating the effects exerted by overexpression of malignant miRNAs is possible through the application of artificial antagonists such as oligonucleotides or other small molecules. It is also possible to supplement miRNAs through the use of synthetic oligonucleotides [36]. In the case of current study, the miRNAs which were found to influence the transcription of upregulated genes in cocaine addiction can be supplemented so that they can negatively regulate those genes and thus reduce the addictive effects.…”
Section: Enrichment Analysismentioning
confidence: 99%
“…Mitigating the effects exerted by overexpression of malignant miRNAs is possible through the application of artificial antagonists such as oligonucleotides or other small molecules. It is also possible to supplement miRNAs through the use of synthetic oligonucleotides [36]. In the case of current study, the miRNAs which were found to influence the transcription of upregulated genes in cocaine addiction can be supplemented so that they can negatively regulate those genes and thus reduce the addictive effects.…”
Section: Enrichment Analysismentioning
confidence: 99%
“…Mitigating the effects exerted by overexpression of malignant miRNAs is possible through the application of artificial antagonists such as oligonucleotides or other small molecules. It is also possible to supplement miRNAs through the use of synthetic oligonucleotides [21]. In the case of current study, the miRNAs which were found to influence the transcription of upregulated genes in cocaine addiction can be supplemented so that they can negatively regulate those genes and thus reduce the addictive effects of cocaine.…”
Section: Enrichment Analysis Of Upregulated Genes Chea2016 Tfsmentioning
confidence: 99%
“…Through their complex, fine-tuned post-transcriptional gene regulation, miRNAs play an important role in the initiation and progression of tumors [21], cardiovascular diseases [22] and other disorders. Since the inception of the role of miRNAs in cancer in 2002, research efforts have mainly been focused on their biological basis, dysregulation in diseases, but also the potential therapeutic value of miRNAs.…”
mentioning
confidence: 99%